PENGARUH GOOD CORPORATE GOVERNANCE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN LQ 45 - Kumalasari, Andini; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of good corporate governance and dividend policy to thefirm value through the annual financial statements which have been prepared by the LQ-45 companies which arelisted in Indonesia Stock Exchange. The good corporate governance mechanism is proxy by managerialownership, institutional ownership, independent commissioner and audit commitee. The population has beenobtained by using purposive sampling method to the LQ-45 companies which are listed in Indonesia StockExchange in 2013-2015 periods and based on the predetermined criteria, 54 companies in LQ-45 have beenselected as samples. The analytical method has been carried out by using multiple linear regression analysis andthe SPSS (Statistical Product and Service Solutions). The result of the research shows that institutionalownership, independent commisioner and dividend policy give positive and significant influence to the firmvalue. The result of managerial ownership shows negative and significant influence to the firm value.Meanwhile, the audit commitee does not give significant influenceto the firm value. Simultaneously,independent variables gives significant influence to the dependent variable.Keywords: good corporate governance, dividend policy, firm value.